A comparison of economy between two different backpack designs for runners. (April 2020) - Scheer, Volker; Vieluf, Solveig; Schröder, Marc; Lappe, Pascal; Heitkamp, Hans-Christian
Abstract: We compared two backpack designs (back/front or back only) in twelve recreational runners (age 22.0 ± 1.7years). An initial incremental exercise test (VO2 max 52.2 ± 4.7 ml kg −1. min −1 ) was conducted, followed by four tests of 20 min duration (running speed 9.8 ± 1.1 km/h) with loads carried of 0, 1 kg, 3 kg, and 6 kg with the two backpack designs in a randomized order. Economy was assessed by energy cost of running (CR), oxygen cost (O2 cost), heart rate (HR) and rate of perceived exertion (RPE). Repeated measure ANOVA revealed a non-significant main effect for CR, O2 cost, HR, RPE between systems. Post-hoc comparison of significant time × position interaction showed for CR, F(3, 33) = 5.34, p < .01, ηp 2  = 0.33, and O2 cost, F(3, 33) = 5.15, p < .01, ηp 2  = 0.32, that carrying weight in the back/front were significantly lower after 20 min (CR: p = .02 and O2 cost: p = .03). These results suggest, that for longer runs the equal distribution of weight is advantageous.